Hukum Positif dan Hukum Islam: Analisis Tata Cara Menemukan Hukum dalam Kacamata Hukum Positif dan Hukum Islam - Arif Sugitanata; Suud Sarim Karimullah; Rizal Al Hamid (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
This paper discusses the analysis of the procedure for finding law in the perspective of positive law and Islamic law, with the main subject of study being how the method or method of finding law in positive law and Islamic law. Utilizing a literature study, of course, primary data comes from books and journals related to the problem being studied. This paper finds that the method of exploring legal discovery in Indonesia can be done both in formal law and material law. Legal discovery in the field of formal law is aimed at overcoming all juridical and technical obstacles and hurdles in order to achieve a simple, fast and low-cost trial without reducing legal protection and fair service for the litigants (Article 59 UU-PA). Legal discovery in the field of material law is aimed at the realization of justice in every case faced. Legal discovery is always related to legal protection and justice services to justice seekers. Legal discovery is always quantitative, realistic, pragmatic and executable. In the realm of Islamic law, the method of finding law is not too different from the method of positive law. Muslim experts have developed the structure of legal discovery (istinbath) as explained by Prof. Syamsul Anwar in his writings such as through linguistic/literal implementation, ta'lili or causation and synchronization or alignment. Coupled with an offer built by Louay Safi with an integrated method of legal discovery. This method combines social-empirical analysis with normative-textual based on two patterns, namely historical inference and textual inference.